Positive impact of a pre-school-based nutritional intervention on children's fruit and vegetable intake: results of a cluster-randomized trial - Bock, Freia de; Breitenstein, Luise; Fischer, Joachim E. (Public health nutrition, 2012)
Objective: To assess the short-term impact of a nutritional intervention aimed at reducing childhood overweight in German pre-school children. Design: Using a cluster-randomized study design with waiting-list controls, we tested a 6-month intervention administered once weekly by a nutrition expert consisting of joint meal preparation and activities for children and parents such as tasting and preparing nutritious, fresh foods. At baseline, 6 and 12 months, a parent-completed questionnaire assessed fruit and vegetable intakes (primary outcomes) and water and sugared drinks consumption (secondary outcomes). Direct measurement assessed BMI, skinfold thickness and waist-to-height-ratio. An intention-to-treat analysis used random-effects panel regression models to assess the intervention effect, adjusted for each child’s age, gender, immigrant background and maternal education. Setting: Eighteen pre-schools from three south German regions. Subjects: Healthy children aged 3-6 years. Results: Three hundred and seventy-seven (80 %) eligible pre-school children participated in the study. Of these, 348 provided sufﬁcient data for analysis. The sample mean age was 4?26 (SD 0?78) years; the majority (53?2 %) were boys. Children’s fruit and vegetable intakes increased signiﬁcantly (P , 0?001 and P , 0?05, respectively); no signiﬁcant changes in the consumption of water, sugared drinks or anthropometric measurements were noted.Conclusions: Nutritional interventions in pre-schools have the potential to change eating behaviours in young children, which in the long term might reduce risk for developing overweight.
First published online 23 August 2011
Gesehen am 21.08.2018